Sistem Informasi Geografis Jumlah Penduduk dan Laju Pertumbuhan Penduduk Terhadap Pertumbuhan Ekonomi di Kabupaten Pati - Rizky Maryam Shinta Mutiara (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study explores the application of Geographic Information System (GIS) in analyzing the population size and growth rate in relation to economic growth at the district level in Pati Regency. The focus is on individual sub-districts within the region. By utilizing GIS, demographic and economic data are mapped and visually represented for each sub-district, offering a profound understanding of the correlation between population and local economic growth. This analysis provides valuable insights for policymakers and researchers to design more effective development strategies.